On the Issue of Increasing the Competitiveness of the Economy of the Republic of Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In the era of globalization and technological advancement, Uzbekistan prioritizes enhancing national competitiveness through deep structural reforms under the “Uzbekistan-2030” strategy. Key goals include digital transformation, innovation, human capital development, and attracting foreign investment. The country aims to join the Top 50 of the Global Innovation Index by 2030 through integrated efforts in education, science, and economic modernization. Uzbekistan is committed to building a robust digital infrastructure, enabling seamless integration of technology across all sectors. The government is encouraging the growth of tech startups, smart city initiatives, and the expansion of e-governance to increase transparency and efficiency. Investments in artificial intelligence, blockchain, and IT parks are laying the foundation for a digital economy that aligns with global standards.